Do Gender, Age, and Education Matter for Guest Loyalty in Four-Star Hotels in Serbia? - Sanja Džever (Anali Ekonomskog fakulteta u Subotici, 2026)
Purpose: This paper examines whether gender, age, and education level introduce systematic differences in post-purchase behaviour among guests of four-star hotels in the Republic of Serbia, with a focus on two distinct outcomes: revisit intention and positive electronic word-of-mouth intention (eWOM), both considered indicators of guest loyalty.Мethodology: Primary data were collected through a survey of 589 respondents who had previously stayed in a four-star hotel in Serbia. Differences between male and female respondents were examined using independent-samples t-tests, whereas differences across age and education groups were analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post hoc test. The practical significance of the observed differences was assessed using eta-squared (η²).Findings: Revisit intention does not differ significantly across gender, age, or education, suggesting that the propensity to return to the same hotel is broadly uniform across socio-demographic groups. Positive electronic word-of-mouth intention is significantly higher among male guests (η² = 0.027) and, in one specific pairwise comparison, among respondents with Bachelor/Higher degrees than among postgraduate degree holders (η² = 0.021), although both effects are small.Originality/value: The paper provides original evidence on socio-demographic differences in guest loyalty in Serbia's four-star hotel sector and contributes to the debate on whether revisit intention and electronic word-of-mouth are driven by the same factors.Practical implications - The findings suggest that socio-demographic characteristics alone are insufficient to explain guest loyalty, indicating the need for future research to investigate the contribution of other factors, such as service quality and customer satisfaction.Limitations: The study relies on a non-probability sample with an overrepresentation of younger, female, and urban respondents, limiting the generalizability of the findings, particularly beyond the Serbian context.